2013
DOI: 10.1121/1.4799813
|View full text |Cite
|
Sign up to set email alerts
|

The value of a kurtosis metric in estimating the hazard to hearing of complex industrial noise exposures

Abstract: A series of Gaussian and non-Gaussian equal energy noise exposures were designed with the objective of establishing the extent to which the kurtosis statistic could be used to grade the severity of noise trauma produced by the exposures. Here, 225 chinchillas distributed in 29 groups, with 6 to 8 animals per group, were exposed at 97 dB SPL. The equal energy exposures were presented either continuously for 5 d or on an interrupted schedule for 19 d. The non-Gaussian noises all differed in the level of the kurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…A window of 40 s was chosen as a compromise that allowed for computational efficiency and reflected the dynamic features of complex noise. The selection of 40-s time window was based on previous animal data with a sampling rate of 48 kHz (Hamernik et al, 2003;Qiu et al, 2007;Qiu et al, 2013), which was found to be sufficient for establishing an acceptable measure of the kurtosis. The mean kurtosis of these 40-s windows was calculated and used as the kurtosis value for the entire shift.…”
Section: Noise Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A window of 40 s was chosen as a compromise that allowed for computational efficiency and reflected the dynamic features of complex noise. The selection of 40-s time window was based on previous animal data with a sampling rate of 48 kHz (Hamernik et al, 2003;Qiu et al, 2007;Qiu et al, 2013), which was found to be sufficient for establishing an acceptable measure of the kurtosis. The mean kurtosis of these 40-s windows was calculated and used as the kurtosis value for the entire shift.…”
Section: Noise Exposure Assessmentmentioning
confidence: 99%
“…The statistical metric kurtosis (b), an index of the extent to which the distribution of a variable deviates from the G, is defined as the ratio of the fourth-order central moment to the squared secondorder central moment of a distribution. The kurtosis (b) can be computed on the amplitude distribution of the temporal waveform of the noise given to the subject or by filtering the waveform, a frequency specific kurtosis [b(f)] can be computed on the resultant time-domain signal (Qiu et al, 2013 More recently, the effects of solvent exposure combined with exposure to two different types of noise with the same spectral composition were compared in experimental studies. The first study with styrene was a 6-h continuous noise of 86.2 dB sound pressure level (SPL) (LEX, 8 h ¼ 85 dB SPL) and complex noise consisting of series of sound bursts at 112 dB (LEX, 8 h ¼ 80 dB SPL).…”
mentioning
confidence: 99%
“…The observed TTS was smaller when the sound consisted of classical music, for the same exposure level and duration (91 dB (A) for two hours). Qiu et al (2013) conclude that the equal energy hypothesis is valid for different exposures when they do not differ too much with respect to the time-pattern of the spectral behavior. They investigated the effect of kurtosis and breaks for equal energy exposures on chinchillas.…”
Section: S47mentioning
confidence: 71%
“…Many of the most important investigations of hearing damage from complex noise have been conducted over recent years by a team of researchers at the State University of New York (SUNY) in Plattsburgh, New York. [9][10][11]55,97,[99][100][101][102][103] These investigations Figure 7 Comparison of histograms from an impulse noise and random noise. The random noise (upper panel) was generated to have the same energy equivalent (L eq ) as the impulse train from a Dillon M134D minigun (lower panel).…”
Section: Use Of Kurtosismentioning
confidence: 99%
“…101 In another more recent investigation involving an even larger number of subjects, Qiu et al exposed 225 chinchillas in 29 groups to uninterrupted noise for 5 days or interrupted noise for 19 days, again to model the work week. 103 There were eight possible combinations of the three parameters of interest-impact interval, peak amplitude, and impact duration-which the large size of the subject population enabled the investigators to study independently. In addition to Gaussian noise, subjects were exposed to kurtosis values of 25, 50, or 100.…”
Section: Use Of Kurtosismentioning
confidence: 99%